Dimensions of precariousness: independent professionals between market risks and entrapment in poor occupational careers. (1st December 2016) - ,; ,; ,
Abstract : This article looks at the multifaceted precariousness of independent professionals through a qualitative analysis based in the urban area of Milan (Italy). It supports the hypothesis that at a more advanced stage of independent professionals' careers, the analysis of precariousness as a market risk can be enriched by adding the concept of 'entrapment' in vulnerable working paths and working and living conditions to the definition of poor occupational careers. Entrapment can be considered as the long-lasting condition of a large and weak part of young-adult independent professionals beyond the first stages of their careers. Our fieldwork confirms the widespread fragmentation of careers and increasing difficulties for young professionals to improve their positions due to structural economic and organisational changes. Four career dynamics of independent professionals emerge from the qualitative analysis – successful, dynamic, entrapped and temporarily interrupted. Career strategies play a major role in determining successful outcomes, but social relations are confirmed as also crucially important for job success, providing professional networks, welfare support and 'local professional integration'.